2018
DOI: 10.1007/s00394-018-1717-y
|View full text |Cite
|
Sign up to set email alerts
|

No improvement in vitamin D status in German infants and adolescents between 2009 and 2014 despite public recommendations to increase vitamin D intake in 2012

Abstract: The increased D-A-CH recommendations for vitamin D intake had no influence on vitamin D levels in children and adolescents. The prevalence of vitamin D deficiency has not changed compared to previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…However, a single study in Malawian pre-school children reported an increase in 25(OH)D levels with age; however, this study was small (n=21) and included infants of mothers living with HIV in Malawi [6]. Studies from high-income countries have reported an increase in 25(OH)D levels with age, but children in these studies received vitamin D supplementation or fortification [34,35,40]. In a meta-analysis of previous studies from Africa, children had higher vitamin D status than adults in African populations [2] possibly due to increased time spent outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…However, a single study in Malawian pre-school children reported an increase in 25(OH)D levels with age; however, this study was small (n=21) and included infants of mothers living with HIV in Malawi [6]. Studies from high-income countries have reported an increase in 25(OH)D levels with age, but children in these studies received vitamin D supplementation or fortification [34,35,40]. In a meta-analysis of previous studies from Africa, children had higher vitamin D status than adults in African populations [2] possibly due to increased time spent outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…Xhu et al revealed that VDD is most severe in late spring and least severe during the summer in preterm births in Northeast China [39]. Low storage of vitamin D in the liver and fat tissue are reasons for low 25(OH)D 3 levels by seasonal change [40]. In this study, we discovered that infants born during the summer and autumn had better vitamin D nutritional status from being born during the sunniest times of the summer and autumn in Northern Taiwan; however, Northern Taiwan is rainy and cloudy in the spring and winter, which reduces exposure to sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have further indicated that vitD deficiency is associated with risks of numerous musculoskeletal, autoimmune, and cardiovascular diseases [ 8 ], as well as cancer, infertility, complications in pregnancy, dementia, and overall mortality (see [ 2 ] for details). Although some researchers have used observational or clinical evidence to argue that vitD has weak or no effect on health issues, ranging from health improvement [ 9 ] to the incidence and mortality of all diseases and general or site-specific cancers [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], the importance of vitD as an essential nutrient for human health is confirmed as general wisdom by scientific evidence [ 2 ].…”
Section: Introductionmentioning
confidence: 99%